2012
DOI: 10.1007/s10995-012-0981-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Once Weekly, Twice Weekly, and Daily Oral Iron Therapy in Jordanian Children Suffering From Iron Deficiency Anemia

Abstract: The efficacy of daily versus twice weekly and once weekly oral iron therapy was analyzed to optimize a protocol for treatment of IDM among Jordanian children. One hundred and forty-eight children aged between 6 and 60 months with Hb estimate less than 11 gm/dl were screened. They were randomly divided into three regimens of oral iron therapy for a period of 12 weeks; a group was supplemented with a single weekly dose of iron; a second group received two doses weekly; and a third group had a daily dose of iron.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
5
8
1
3
Order By: Relevance
“…Experimental evidence suggests that taking iron two to three times a day may not be the best way to take iron supplements despite it being the current guidelines. Moretti et al 2015 [33] found that high doses of oral iron supplements cause an increase in hepcidin, which inhibits iron absorption for up to 24 h. They found that dosing 48 h apart enhanced iron absorption compared to three daily doses as it allows sufficient time for hepcidin levels to decrease and remove the mucosal block on absorption [34,35]. Other groups have also confirmed enhanced iron absorption with single dosing once daily or alternate day dosing [33,34,36].…”
Section: Increase Absorption Decrease Absorptionmentioning
confidence: 98%
See 1 more Smart Citation
“…Experimental evidence suggests that taking iron two to three times a day may not be the best way to take iron supplements despite it being the current guidelines. Moretti et al 2015 [33] found that high doses of oral iron supplements cause an increase in hepcidin, which inhibits iron absorption for up to 24 h. They found that dosing 48 h apart enhanced iron absorption compared to three daily doses as it allows sufficient time for hepcidin levels to decrease and remove the mucosal block on absorption [34,35]. Other groups have also confirmed enhanced iron absorption with single dosing once daily or alternate day dosing [33,34,36].…”
Section: Increase Absorption Decrease Absorptionmentioning
confidence: 98%
“…Overall, changing the formulation of iron supplementation reduces side effects by lowering the dosage and, in turn, reduces the amount of unabsorbed iron in the GI tract. It appears the best way to restore iron levels with the least number of side effects is with fewer doses of iron (even just two doses per week), which would also be more cost effective [35].…”
Section: Increase Absorption Decrease Absorptionmentioning
confidence: 99%
“…Hb value may normalize on a small daily dose of iron, but this low dose seldom suffices for metabolic needs or the replenishment of iron stores in the body [13]. Similar studies of iron supplementation in children have reported higher efficacies within a 3-month supplementation period; however, much higher doses of iron (ranging from 2 mg/kg of iron per body weight per day to 6 mg/kg of iron per body weight per day) than the one applied in our study have been used [14][15][16]. Of particular importance, these studies were all performed in anemic subjects, whereas our study included children with ID without anemia.…”
Section: Discussionmentioning
confidence: 68%
“…Profilaktik olarak kullanılan demir günlük olarak oral yolla verilmektedir (günlük demir profilaksisi). Son zamanlarda intermitan demir profilaksisi olarak adlandırılan haftada bir veya iki kez demir kullanımının da etkin olduğunu bildiren çalışmalar yayınlanmaktadır (13)(14)(15)(16). Oral yoldan alınan demirin ilk dozundan sonra enterositlerden demir ve diğer minerallerin emiliminin geçici olarak blokaja uğramasından dolayı günlük demir kullanımı ile intermitan demir kullanımlarının benzer şekilde barsaktan emildiğini bildiren çalışmalar vardır (17,18).…”
Section: Discussionunclassified